2009
DOI: 10.1098/rspa.2009.0453
|View full text |Cite
|
Sign up to set email alerts
|

A glance beyond the quantum model

Abstract: One of the most important problems in physics is to reconcile quantum mechanics with general relativity, and some authors have suggested that this may be realized at the expense of having to drop the quantum formalism in favour of a more general theory. Here, we propose a mechanism to make general claims on the microscopic structure of the Universe by postulating that any post-quantum theory should recover classical physics in the macroscopic limit. We use this mechanism to bound the strength of correlations b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
349
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(358 citation statements)
references
References 24 publications
6
349
0
1
Order By: Relevance
“…Indeed, the existence of a global probability distribution excludes violation of a Bell inequality, hence guarantees the existence of a local model [12]. This also establishes the connection with the concept of macroscopic-locality [1].…”
Section: Macroscopic Limit Of Isotropic Pr-boxesmentioning
confidence: 78%
See 2 more Smart Citations
“…Indeed, the existence of a global probability distribution excludes violation of a Bell inequality, hence guarantees the existence of a local model [12]. This also establishes the connection with the concept of macroscopic-locality [1].…”
Section: Macroscopic Limit Of Isotropic Pr-boxesmentioning
confidence: 78%
“…This is true as well for quantum systems as for systems described by any post-quantum theory. In section III we illustrated this for large ensembles of spin- 1 2 and showed that indeed, the quantum formalism of weak measurement provides the tool to describe collective measurements and how they carefully are just at the border of not violating the no-signaling principle. In the following section we considered noisy PR-boxes, that is hypothetical boxes with stronger than quantum correlations.…”
Section: Conclusion and Open Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous principles cannot rule out the existence of sets of correlations strictly larger than the quantum one for any single experiment [6][7][8][9][10][11][12][13][14], we have shown that, for self-complementary graphs, the E principle, by itself, excludes any set of correlations strictly larger than the quantum set.…”
mentioning
confidence: 99%
“…One consists of reconstructing QT as a purely operational probabilistic theory that follows from some sets of axioms [1][2][3][4][5]. A second approach consists of identifying principles that explain the set of quantum nonlocal correlations [6][7][8][9][10][11][12][13][14]. The third approach consists of identifying principles that explain the set of quantum contextual correlations [15][16][17][18][19] without restrictions imposed by a specific experimental scenario [20][21][22][23].…”
mentioning
confidence: 99%